New Prospective for Enhancement in Bioenergy Resources Through Fungal Engineering - Azmat, Rafia; Moin, Sumeira; Saleem, Ailyan; Hamid, Neelofer; Khursheed, Anum; Ahmed, Waseem (Recent Patents on Biotechnology, 2018)
Background: Lignin and cellulose, organic constituents of the plant or plant-based material not commonly used for feeding purpose are referred as Biomass. Patents suggest that this can be used as the best resource of renewable energy. Vesicular Arbuscular Mycorrhizae (VAM) fungi can play an effective role in biomass manufacturing through activated metabolism of the plant under dual symbiosis. During C acclimatization, mycorrhizal inoculated plants existent greater number of leaves with a height of plants as compared to non-mycorrhizal plants. The current article discloses the search of the natural resources for C assimilation into biomass using mycorrhizal symbiosis. Methods: The pot experiment was conducted in the natural environment for extraction of more bioenergy through biomass of Conocarpus erectus L under VAM (Glomus fasciculatum) inoculation in various environmental conditions with replicates. Results: It observed that these fungal engineered plants showed distinctive prospective to offer, enhanced biomass to energy couple with a strong network for sinking CO2 from the atmosphere via strong roots and large surface area of leaves. There was an increase in biomass (9-17% respectively) of the plant under drought-VAM, VAM inoculation and VAM- enriched CO2 conditions in same period in comparison to control plants through lignin, cellulose and carbohydrate contents. It was followed by enhanced enzyme activities and nutrient ions in dual symbiosis. Conclusion: Coupling biomass-originated energy may recover environmental conditions and commercial value for sustainable growth in energy consumption sector. The green energy from fungal engineered plants may replace high demand of fossil fuel as a young biofuel and make the cities more productive in the fabrication of bioenergy too in the form of biomass or biofuel with C impartial atmosphere.
Keywords: mycorrhizal symbiosis